Theorizing the (Un)Sounded in Sikhī: Anhad, Sabad, and Kīrtan - Inderjit N. Kaur (MDPI AG, 2021)
Listening to sabad kīrtan (sung scriptural verse) is a core, everyday, widespread, and loved worship practice of Sikhs around the globe. Thus, it would be fair to state that sounding is central to Sikh worship. Indeed, the Sikh scripture considers kīrtan to be an eminent mode of devotion. Yet, the ultimate aim of this sonic practice is to sense the “unsounded” vibration—anhad—and thereby the divine and divine ethical virtues. Based on a close reading of Sikh sacred texts and ethnographic research, and drawing on the analytic of transduction, the paper explicates the embodied vibratory dimensions of the (unsounded) anhad and (sounded) sabad kīrtan. It argues that the central purpose of the Sikh (un)sounding perceptual practice is embodied ethical attunement for an unmediated experience of the divine and divine ethical virtues, and thereby the development of an ethical life. At the intersection of music, sound, religious, and philosophical studies, the analysis reveals the centrality of the body in worship and ethical development, and contributes to interdisciplinary conversations on sensory epistemologies in faith traditions.